2009
DOI: 10.1111/j.1399-0039.2009.01390.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of HLA class I gene is associated with HLA class I down‐regulation in human gastric cancer

Abstract: Down-regulated expression of human leukocyte antigen (HLA) class I molecules in many human cancers facilitate tumor cells to escape from immune attack. Promoter hypermethylation, one of the major epigenetic changes responsible for gene inactivation, plays an important role in gastric carcinogenesis. This study evaluated the expression and alteration of HLA class I molecules in a panel of 47 pairs of gastric cancer specimens with their noncancerous parts from Chinese patients by using immunohistochemistry (IHC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 27 publications
(31 reference statements)
0
37
0
Order By: Relevance
“…57 Other studies have found DNA methylation of such genes in association with gastric cancer (HLA-C 58 ) and type 1 diabetes (HLA-DQB1 and HLA-DRB1 59 ). Interestingly, Ye and colleagues 58 found that HLA-C promoter methylation patterns were also associated with age and gender (higher methylation rates negatively associated with age in males). The present twin study suggests that environmental epigenetic processes may drive some of the variation in HLA functions (irrespective of DNA sequence) that are already associated with inter-individual differences in susceptibility to disease in adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…57 Other studies have found DNA methylation of such genes in association with gastric cancer (HLA-C 58 ) and type 1 diabetes (HLA-DQB1 and HLA-DRB1 59 ). Interestingly, Ye and colleagues 58 found that HLA-C promoter methylation patterns were also associated with age and gender (higher methylation rates negatively associated with age in males). The present twin study suggests that environmental epigenetic processes may drive some of the variation in HLA functions (irrespective of DNA sequence) that are already associated with inter-individual differences in susceptibility to disease in adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…There was no correlation between methylation and HLA-G gene expression in ovarian tumor samples and OSE, which suggested that changes in methylation may be necessary, but not sufficient, for HLA-G expression in ovarian cancer (Menendez et al, 2008). In addition, the expression of HLA-A, HLA-B and HLA-C, specific ligands for inhibitory KIR (KIR3DL2, KIR3DL1, and KIR2DL1/3) was lost or downregulated in human gastric cancer, where the percentage of promoter methylation was higher than in adjacent nontumor tissues (Ye et al, 2010). In esophageal squamous cell carcinoma lesions, it was also shown that hypermethylation in the gene promoter regions of the HLA-A, HLA-B and HLA-C, and altered chromatin structure of the HLA class I heavy chain gene promoters have both been implicated as a major mechanism for transcriptional inactivation of HLA genes (Nie et al, 2001).…”
Section: Hla-ligand Of Kirmentioning
confidence: 89%
“…Methylation within the HLA-A, -B or -C loci has been found, e.g. in oesophagus carcinomas (Nie et al 2001(Nie et al , 2002, in gastric and cervical cancer (Ye et al 2010;De Lourdes et al 2006). Our current observations suggest that also in colorectal cancer HLA-B is most likely downregulated via DNA methylation, while HLA-A seems to be regulated in a different way.…”
Section: Msldr Detects Specific Methylation Within Hla Ulbp and Apm mentioning
confidence: 97%